2012
DOI: 10.7589/0090-3558-48.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Immobilization of Raccoons (Procyon Lotor) With Ketamine-Medetomidine Mixture and Reversal With Atipamezole

Abstract: ABSTRACT:Safe and reliable capture techniques for wild animals are important for ecologic studies and management operations. We assessed the efficiency of ketamine-medetomidine (K:M) injection and reversal with atipamezole. We anesthetized 67 raccoons (Procyon lotor; 34 males, 33 females) 103 times (individuals captured between one and five times) from April 2009-October 2010 in Mont-Orford Provincial Park, Quebec, Canada. We administered a 1:1 mixture by volume of ketamine and medetomidine by intramuscular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
2
12
1
1
Order By: Relevance
“…Similar results have been observed in Polar Bears, Sika (Cervus Nippon), Eurasian Otter, European Mink, European Polecat and Raccoons (Cattet et al 1997;Tsuruga et al 1999;Fernandez-Moran et al 2001;Fournier-Chambrillon et al 2003;Robert et al 2012). This was expected as atipamezole hydrochloride fully antagonizes the sedative and behavioural effects of medetomidine hydrochloride when administered at four to six times the medetomidine hydrochloride dose (Sinclair 2003).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Similar results have been observed in Polar Bears, Sika (Cervus Nippon), Eurasian Otter, European Mink, European Polecat and Raccoons (Cattet et al 1997;Tsuruga et al 1999;Fernandez-Moran et al 2001;Fournier-Chambrillon et al 2003;Robert et al 2012). This was expected as atipamezole hydrochloride fully antagonizes the sedative and behavioural effects of medetomidine hydrochloride when administered at four to six times the medetomidine hydrochloride dose (Sinclair 2003).…”
Section: Discussionsupporting
confidence: 67%
“…This has been observed in seals and raccoons, where repeated exposure to ketamine and medetomidine increased induction time (Field et al 2002;Wheatley et al 2006;Robert et al 2012). In this study, an increase in induction during the second KX treatment was observed; however, no significant difference in induction time was observed in the KM group.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Traps were checked daily and each capture location was recorded with the use of a handheld global positioning system (GPS) unit. Raccoons and skunks were anesthetized following methods described by Robert et al (2012). Each animal was sexed and ear-tagged for identification.…”
Section: Post-orv Monitoringmentioning
confidence: 99%